The body as capital : masculinities in contemporary Latin American fiction - Venkatesh, Vinodh (The University of Arizona Press, 2015)
"The book analyzes the notion of the male body as a dialogic site of enunciation, arguing that the writing of masculinities is a project centering socioeconomic and political concerns, anxieties, and paradigms on the male anatomy and on masculinities presented in fiction, forging a new path in the critical debates over gender and sexuality in Latin American writing"--Provided by publisher.